Evolutionary diversification of aminopeptidase N in Lepidoptera by conserved clade-specific amino acid residues - Hughes, Austin L. (Molecular phylogenetics and evolution, 2014)
[Display omitted] •The aminopeptidase N (APN) genes of Lepidoptera underwent ancient duplications.•APN1 was the most generalized APN class.•Class-specific conserved derived residues suggest sequence specialization.•APN2, APN6, and APN8 were most specialized in sequence.•APN2, APN6, and APN8, shared a convergently evolved residue near the active site. Members of the aminopepidase N (APN) gene family of the insect order Lepidoptera (moths and butterflies) bind the naturally insecticidal Cry toxins produced by the bacterium Bacillus thuringiensis. Phylogenetic analysis of amino acid sequences of seven lepidopteran APN classes provided strong support for the hypothesis that lepidopteran APN2 class arose by gene duplication prior to the most recent common ancestor of Lepidoptera and Diptera. The Cry toxin-binding region (BR) of lepidopteran and dipteran APNs was subject to stronger purifying selection within APN classes than was the remainder of the molecule, reflecting conservation of catalytic site and adjoining residues within the BR. Of lepidopteran APN classes, APN2, APN6, and APN8 showed the strongest evidence of functional specialization, both in expression patterns and in the occurrence of conserved derived amino acid residues. The latter three APN classes also shared a convergently evolved conserved residue close to the catalytic site. APN8 showed a particularly strong tendency towards class-specific conserved residues, including one of the catalytic site residues in the BR and ten others in close vicinity to the catalytic site residues. The occurrence of class-specific sequences along with the conservation of enzymatic function is consistent with the hypothesis that the presence of Cry toxins in the environment has been a factor shaping the evolution of this multi-gene family.